Pelatihan Metode Pembelajaran Aktif, Inovatif dan Menyenangkan untuk Guru MI Bahrul Ulum Nataan Gedong Boyountung Lamongan - Azizah, Mar'atul; Hasan, Moch. Sya'roni; Budiyono, Ahmad; Sirojuddin, Akhmad; Rofiq, Ainur (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
This service aims to improve teachers' competence in implementing active, innovative, creative, effective and fun (PAIKEM) learning methods through training for 15 teachers of MI Bahrul Ulum Nataan. Online training was carried out through 4 session meetings by applying various training methods. The results of the training showed a significant increase in understanding of PAIKEM concepts (62% to 89%), skills in implementing PAIKEM methods (69% to 91%), and creativity in developing innovative learning (65% to 85%) in the trained teachers. The application of PAIKEM by teachers impacts the increase in student activity and learning outcomes as well as the positive image of schools. In conclusion, PAIKEM training is able to improve teacher professional competence and contribute significantly to improving the quality of learning at MI Bahrul Ulum Nataan.